Polymeric and Lipid Nanoparticles: Which Applications in Pediatrics? - Noelia Nieto González; Antonella Obinu; Giovanna Rassu; Paolo Giunchedi; Elisabetta Gavini (MDPI AG, 2021)
This review aims to provide the state of the art on polymeric and lipid nanoparticles, used or suggested to approach pediatric diseases' problems and needs, and to inspire new researches in this field. Several drugs are currently not available in formulations suitable for pediatric patients. The United States Pediatric Formulation Initiative suggested applying new technologies to pediatric drug formulations, for instance, nanotechnology. The literature analysis showed that polymeric and lipid nanoparticles have been widely studied to treat pediatric diseases, and albumin nanoparticles and liposomes are already used in clinical practice. Nevertheless, these studies are focused almost exclusively on pediatric cancer treatment. Although nanomedicine may solve many needs of pediatric diseases and medicines, the unavailability of data on pharmacokinetics, safety and efficacy of both drugs and nanoparticles in pediatric patients limits the development of new pediatric medicines based on nanoparticles. Therefore, nanomedicine applied in pediatrics remains a significant challenge in the near future.